Ultrasonographic Evaluation of Hernioplasty of Experimentally Induced Large Ventro-lateral Hernia in Bucks - Hummadi, Saddam K.; AL-Asadi, Rahi N. (The Iraqi Journal of Veterinary Medicine, 2011)
The present study is assigned to evaluate the efficiency of hernioplasty in reconstruction of experimentally induced ventro-lateral hernia in bucks using two types of sutures (silk and polypropylene) and to find which thread is more safe and suitable for closure of the hernia, based on ultrasonographic examination.Sixteen adult local breed bucks were enrolled for this study. All subjected to inducing artificial ventro-lateral hernia (12x10) cm in the right flank under the effect of local anesthesia (2% Lidocaine), then left for one month. After that, animals divided randomly and equally into two groups. In the first group, hernia repaired with silk, while in the second group, hernia closed by polypropylene. Sewing technique is used in both groups. The final appearance was (mesh-like).Ultrasonographic examination in silk group and after 2 months there was slight improvement in echogenecity and collagen fibers. Polypropylene group and at the same period revealed an increased in echogenecity and decreased lesion size earlier in compare with silk group. In 4 months polypropylene group, reflected high echogenecity and complete infilling of the sewing holes with mature collagen fibers.